COMPARISON OF LATANOPROST AND DORZOLAMIDE IN THE TREATMENT OF PATIENTS WITH OPEN ANGLE GLAUCOMA - Niazi, Muhammad Khizar; Raja, Naseer (Journal of Ayub Medical College Abbottabad, 2004)
Background: This study was conducted to compare the effects on intraocular pressure and side effects of monotherapy with either latanoprost or dorzolamide in patients with open angle glaucoma, pseudoexfoliation glaucoma or ocular hypertension. Methods: Sixty patients with open angle glaucoma or ocular hypertension were recruited to a 3-month study. Previous glaucoma medications were washed out and the patients were randomised to receive either latanoprost 0.005% once daily or dorzolamide 2% three times daily. The follow-up visits were conducted at two weeks, one months and three months of study and intraocular pressures and slit lamp examinations were carried out to look for response of therapy and detect complications. Results: After 3 months, latanoprost reduced mean baseline intraocular pressure from 27.2±3.0 mm Hg by 8.5±3.3 mm Hg. The corresponding figures for dorzolamide were 27.2±3.4 and 5.6±2.6 mm Hg. The difference of 2.9 mm Hg (95% CI: 2.3-3.6) was highly significant (p<0.001). Both drugs were well tolerated systemically and locally. Conclusion: Latanoprost was superior to dorzolamide in reducing the intraocular pressure, judged from the effect on mean intraocular pressure. The once daily dose in the evening ensures better compliance and the problem of hyperpigmentation of the iris were not encountered. Keywords: Glaucoma, Intraocular pressure, Latanoprost, Dorzolamide